2015
DOI: 10.1111/lam.12495
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel 2,3-butanediol dehydrogenase/acetoin reductase from Corynebacterium crenatum SYPA5-5

Abstract: Acetoin and 2,3-butanediol are commonly used as platform chemicals and widely used in pharmaceutical industries. 2,3-butanediol dehydrogenase/acetoin reductase (2,3-BDH/AR) plays a significant role in the microbial production of acetoin and 2,3-butanediol. In this study, 2,3-BDH was cloned from Corynebacterium crenatum SYPA5-5, was expressed in Escherichia coli BL21 and characterized with respect to the optimal temperature, pH, substrate specificity and kinetics. The results will guide further studies in Coryn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The presence of ions could act as inhibitors of specific enzymatic activities . The BDO dehydrogenases activity from Corynebacterium crenatum was increased by Ca 2+ , Mg 2+ , Zn 2+ and Mn 2+ ions, besides Cu 2+ that inhibited BDH activity . Yu et al reported and characterized the (2R,3R)‐BDH from Rhodococcus erythropolis .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of ions could act as inhibitors of specific enzymatic activities . The BDO dehydrogenases activity from Corynebacterium crenatum was increased by Ca 2+ , Mg 2+ , Zn 2+ and Mn 2+ ions, besides Cu 2+ that inhibited BDH activity . Yu et al reported and characterized the (2R,3R)‐BDH from Rhodococcus erythropolis .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, compared to C. crenatum WT, C. crenatum SDA showed a high AR and BDH activities (0.32 and 0.10 U mg −1 ) comparable to C. crenatum A (0.38 and 0.19 U mg −1 ). In addition, although AR/BDH was a bidirectional reversible enzyme [24, 27], the heterogenous AR/BDH from B. subtilis present a higher AR activity than BDH activity in C. crenatum A and C. crenatum SDA. With ALS, ALDC, and (or) AR/BDH, the recombinant C. crenatum can catalyze the pyruvate to either AC or DA, thus allowing the respective conversion of glucose to AC and 2,3-BD.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the spontaneous non-enzymatic decarboxylation reaction of α -acetolactate under natural oxidative aerobic conditions [31]. In addition, our previous work has also proved that the BDH from C. crenatum could catalyze DA to AC and then convert to 2,3-BD [24]. This explains why the chain reaction was got through in C. crenatum S without expression of ALDC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence analysis method, for the analysis and detection of equipment fault diagnosis, collects the temperature sequence of the normal and stable operation of the equipment, puts each temperature value collected into the database as a sample, and establishes a standard data sample database, thus completing the diagnosis and detection of the fault [13]. This method is applied to the fault identification and analysis of the airborne circuit board of the boiler plant equipment.…”
Section: Sequence Analysismentioning
confidence: 99%